Passivation process of perovskite layer and preparation process of perovskite solar cell
During the preparation of perovskite solar cells, the bonding transfer technology of the source substrate with a passivator layer and the semi-finished solar cell is used to solve the problems of uneven passivation processes, waste of resources and low production efficiency, and the uniformity and production efficiency of the passivation layer are improved.
Patent Information
- Application Number
- CN202411849634.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
AI Technical Summary
The passivation process of existing perovskite solar cells has problems such as unevenness, waste of resources and low production efficiency, which affects the efficiency and stability of the battery.
A passivation process is adopted to bond the source substrate with the passivation agent layer to the semi-finished solar cell cell, and the passivation agent layer is transferred to the perovskite layer through transfer technology to form a uniform passivation layer. The process includes transferring at a temperature of 20 to 110°C, and the pressure can reach 0 to 1000Mpa.
This process simplifies the operation process, reduces the use of passivating agent, avoids resource waste, significantly shortens passivation time, and improves production efficiency. At the same time, the uniform passivation layer improves the efficiency and stability of solar cells and promotes its industrialization process.
Smart Images

Figure CN119767993A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a passivation process for a perovskite layer and a preparation process for a perovskite solar cell. Background Art
[0002] In the preparation process of perovskite solar cells, the passivation step is a key link, which directly affects the efficiency and stability of the cell. There are a large number of defects inside, on the surface and at the interface of the perovskite film. These defects will capture carriers, affect the efficiency of the cell, and are related to the perovskite hysteresis phenomenon. Therefore, passivating defects can not only improve efficiency, but also significantly reduce hysteresis.
[0003] At present, although there are many passivation methods, such as spin coating, coating, vapor phase method and immersion method, each of these methods has its own limitations. Spin coating causes uneven passivation and material waste due to uneven centrifugal and centripetal forces; coating causes uneven passivation due to the excessively fast evaporation rate of the solvent of the passivation molecules; although vapor phase method and immersion method can achieve uniform passivation, they are neither environmentally friendly nor easy to control the passivation time, affecting the production cycle of components.
[0004] In the actual preparation process, the direct contact between the machine and the perovskite layer may cause wear and uneven passivation of the perovskite layer. In addition, the passivation process takes a long time, which makes the passivation step a limiting step or bottleneck step in the entire preparation process. This limitation not only affects the industrialization process of solar cells, but is also a key factor in determining the final quality of solar cells. Therefore, improving the passivation step is of great significance to improving the quality and production capacity of solar cells.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the objectives of the present invention is to provide a passivation process for a perovskite layer to solve at least one of the above-mentioned technical problems in the prior art.
[0007] A second object of the present invention is to provide a process for preparing a perovskite solar cell.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] The first aspect of the present invention provides a passivation process for a perovskite layer, wherein a source substrate with a passivator layer is laminated to a semi-finished solar cell, and the passivator layer is transferred to the surface of the semi-finished solar cell to obtain the passivation layer;
[0010] The surface layer of the semi-finished solar cell sheet is a perovskite layer.
[0011] Furthermore, the transfer temperature is 20-110°C.
[0012] Preferably, the transfer pressure is 0-1000 MPa.
[0013] Preferably, the conductive substrate of the semi-finished solar cell sheet comprises ITO glass or FTO glass, preferably ITO glass.
[0014] Preferably, the source substrate is made of ITO glass or FTO glass, preferably ITO glass.
[0015] Preferably, the surface of one side with the passivator layer is placed on the surface of the perovskite layer, and the passivator layer is transferred to the perovskite layer by heating or pressurizing on the source substrate to obtain the passivation layer.
[0016] A second aspect of the present invention provides a process for preparing a perovskite solar cell, comprising the passivation process.
[0017] The preparation process of the perovskite solar cell is to prepare a hole transport layer and a perovskite layer in sequence on a pretreated conductive substrate to obtain a semi-finished solar cell sheet;
[0018] Then, a passivation layer, an electron transport layer, a hole blocking layer and a deposited metal electrode are prepared in sequence on the semi-finished solar cell sheet to obtain the perovskite solar cell.
[0019] Furthermore, the pretreatment process includes performing P1 scribing, cleaning, drying and activation processes on the conductive substrate.
[0020] Preferably, the laser frequency of the P1 scribing is 50-500 kHz, and the laser energy is 20-100 μJ.
[0021] Preferably, the width of the P1 scribing line is 80-300 μm, and the speed is 100-300 mm / s.
[0022] Preferably, the cleaning reagents include a cleaning solution specifically for conductive glass, deionized water and an organic solvent used in this order.
[0023] Preferably, the organic solvent comprises isopropanol and / or acetone.
[0024] Preferably, the cleaning time of each cleaning reagent is 15 to 25 minutes.
[0025] Preferably, the drying method includes drying by oven or drying by air gun.
[0026] Preferably, the drying temperature is 60-80° C. and the drying time is 18-36 hours.
[0027] Preferably, the activation method includes activation by ultraviolet ozone machine or cleaning activation by plasma cleaning machine.
[0028] Preferably, the activation time is 5 to 20 minutes.
[0029] Furthermore, the preparation method of the hole transport layer is:
[0030] The hole transport layer solution is coated on the pretreated conductive substrate by slit coating, spin coating, magnetron sputtering, scraping, inkjet printing or atomic layer deposition, and then annealed to obtain the hole transport layer.
[0031] Preferably, the hole transport layer is made of Me-4PACz, PTAA, PETDOS:PSS, CuPc, poly-TPD, 2PACz, MeO-4PADBC or nickel oxide.
[0032] Preferably, the solvent in the hole transport layer solution includes at least one of methanol, chloroform, 2-ME and DMF.
[0033] Preferably, the annealing temperature is 80-120° C. and the annealing time is 8-12 min.
[0034] Furthermore, the preparation method of the perovskite layer is:
[0035] The perovskite precursor solution is coated on the hole transport layer by slit coating, vacuum evaporation, magnetron sputtering, inkjet printing or doctor blade coating, and then high and low temperature annealing is performed to obtain the perovskite layer.
[0036] Preferably, the high and low temperature annealing method is to first perform low temperature annealing and then perform high temperature annealing.
[0037] Preferably, the low-temperature annealing is performed at a temperature of 60 to 80° C. and for a time of 8 to 12 minutes.
[0038] Preferably, the high temperature annealing is performed at a temperature of 140 to 160° C. and for a time of 8 to 12 minutes.
[0039] Preferably, the perovskite precursor solution comprises at least one of methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide.
[0040] Preferably, the solvent in the perovskite precursor solution includes at least one of DMF, NMP, DMSO and DMPU.
[0041] Furthermore, the preparation method of the electron transport layer is:
[0042] The electron transport layer material is deposited on the passivation layer by vacuum evaporation, magnetron sputtering or atomic layer deposition to obtain the electron transport layer.
[0043] Preferably, the thickness of the electron transport layer is 20-60 nm.
[0044] Preferably, the electron transport layer material includes C60, PCBM, titanium dioxide, zinc oxide or tin dioxide.
[0045] Furthermore, the preparation method of the hole blocking layer is:
[0046] The hole blocking layer material is deposited on the electron transport layer by vacuum evaporation or atomic layer deposition to obtain the hole blocking layer.
[0047] Preferably, the hole blocking layer has a thickness of 6-7 nm.
[0048] Preferably, the hole blocking layer material includes BCP or tin dioxide.
[0049] Furthermore, the preparation process of the perovskite solar cell also includes P2 scribing after preparing the hole blocking layer and before depositing the metal electrode.
[0050] Preferably, the laser frequency of the P2 scribing is 50-500 kHz, and the laser energy is 20-100 μJ.
[0051] Preferably, the width of the P2 scribing line is 40-300 μm, and the speed is 50-500 mm / s.
[0052] Preferably, the electrode material is deposited by vacuum evaporation to obtain the metal electrode.
[0053] Preferably, the thickness of the metal electrode is 50-200 nm.
[0054] Preferably, the electrode material includes copper, silver or gold.
[0055] Compared with the prior art, the present invention has at least the following beneficial effects:
[0056] The passivation process provided by the present invention can effectively passivate the corresponding perovskite layer by only coating a passivator layer on the source substrate, which not only simplifies the operation process, but also reduces the amount of passivator used and avoids waste of resources. The application of this single-layer passivator layer ensures the uniformity of the passivation layer by accurately controlling the amount of the passivator, and avoids the unevenness problem caused by multiple coatings or too fast solvent evaporation. The passivation process only takes 5 to 10 minutes, which greatly shortens the passivation time. This rapid passivation process not only improves production efficiency, but also can be seamlessly embedded in the preparation process of perovskite film, making the entire production process more compact and efficient, not only improving the performance and stability of perovskite solar cells, but also paving the way for large-scale commercial production of perovskite solar cells.
[0057] The preparation process provided by the present invention, in view of the advantages brought by the above-mentioned passivation process, enables the passivation layer to reduce the recombination phenomenon of electrons on the battery surface, significantly improving the efficiency of solar cells; at the same time, the passivation layer reduces the surface defect density of the battery, reduces the chance of electrons and holes recombination on the surface, thereby improving the performance of the battery. Cooperating with other functional layers, the photoelectric conversion efficiency and battery stability are improved, the production cost is reduced, and the production time is shortened, the production efficiency is improved, and the environmental adaptability and reliability of the battery are enhanced by simplifying and integrating the passivation steps, providing strong support for the large-scale commercial production and technical application of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0059] Figure 1 A schematic diagram of the passivation process provided by the present invention;
[0060] Figure 2 This is the fluorescence spectrum obtained in Test Example 1;
[0061] Figure 3 This is the IV curve obtained in Test Example 2. DETAILED DESCRIPTION
[0062] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but those skilled in the art will understand that the following embodiments and examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0063] The "perovskite solar cell" or "perovskite cell" mentioned below in the present invention includes but is not limited to formal perovskite cells, formal perovskite modules, inverted perovskite cells, inverted perovskite modules, small-area perovskite cells, small-area perovskite modules, single-junction perovskite cells, single-junction perovskite modules, perovskite-organic stacked cells, perovskite-organic stacked modules, perovskite-perovskite stacked cells, perovskite-perovskite stacked modules, perovskite-crystalline silicon stacked cells, perovskite-crystalline silicon stacked modules, perovskite-copper indium gallium tin stacked cells, and perovskite-copper indium gallium tin stacked modules.
[0064] The first aspect of the present invention provides a passivation process for a perovskite layer, wherein a source substrate with a passivator layer is laminated to a semi-finished solar cell, and the passivator layer is transferred to the surface of the semi-finished solar cell to obtain the passivation layer;
[0065] The surface layer of the semi-finished solar cell sheet is a perovskite layer.
[0066] The passivation process provided by the present invention can effectively passivate the corresponding perovskite layer by only coating a passivator layer on the source substrate, which not only simplifies the operation process, but also reduces the amount of passivator used and avoids waste of resources. The application of this single-layer passivator layer ensures the uniformity of the passivation layer by accurately controlling the amount of the passivator, and avoids the unevenness problem caused by multiple coatings or too fast solvent evaporation. The passivation process only takes 5 to 10 minutes, which greatly shortens the passivation time. This rapid passivation process not only improves production efficiency, but also can be seamlessly embedded in the preparation process of perovskite film, making the entire production process more compact and efficient, not only improving the performance and stability of perovskite solar cells, but also paving the way for large-scale commercial production of perovskite solar cells.
[0067] By using an automated device to precisely fit the substrate coated with the passivator onto the perovskite film, production efficiency can be further improved, errors caused by human operation can be reduced, and consistency of product quality can be ensured. At the same time, the passivation method of this solution also takes into account the flexibility in actual production, and can be applied to both automated and non-automated production lines. This highly versatile passivation method allows production environments of different scales and conditions to benefit from the optimization of this solution, and can achieve efficient and uniform passivation effects in both large-scale industrial production and small-scale laboratory preparation.
[0068] It should be noted that the present invention is not limited to a specific type of passivator. Any passivator that can be used in perovskite solar cells to passivate perovskite defects can be used. Typical but non-restrictive passivators include but are not limited to quaternary ammonium salt molecules such as phenethylammonium iodide, 4-trifluoromethylphenethylamine iodide, cycloheximide-N-nitrobenzoate, ethylenediamine iodine, propylenediamine iodine, butylenediamine iodine or ethylenediamine iodine, as well as various organic small molecules containing PO bonds, SH, NH bonds, etc., and various inorganic halides, such as zinc chloride, zinc iodide, cadmium iodide, etc.
[0069] The preparation process of the source substrate with the passivator layer is as follows: a layer of passivator molecules is formed on the source substrate by slit coating, scraping, spraying, screen printing, inkjet printing, roll-to-roll printing or vacuum deposition to obtain the source substrate with the passivator layer.
[0070] There are usually uncoordinated metal ions and halogen ions on the surface of perovskite materials. These uncoordinated ions can act as traps to capture carriers, leading to carrier recombination and affecting the performance of the battery. The passivator molecules form strong chemical bonds with these uncoordinated metal ions or halogen ions through their functional groups, effectively passivating these surface defects. The formation of this chemical bond can be a covalent bond, an ionic bond, or a hydrogen bond, etc., depending on the chemical properties of the passivator molecules and the perovskite surface defects.
[0071] In contrast, the interaction between the passivator molecules and the source substrate is weaker because the surface of the source substrate is relatively smooth and its chemical properties have weaker interactions with the functional groups of the passivator molecules. This design makes the passivator molecules prefer to bind to defect sites on the perovskite surface rather than interacting strongly with the source substrate.
[0072] Under the conditions of applying a certain temperature and pressure, the migration and transfer of the passivator molecules are further promoted. The increase in temperature can increase the thermal motion of the molecules, making it easier for the passivator molecules to detach from the source substrate and migrate to the surface of the perovskite film. At the same time, the application of pressure helps to push the passivator molecules into closer contact with the perovskite surface defects, enhancing the interaction between them.
[0073] Furthermore, the transfer temperature is 20-110°C.
[0074] Typically but not limiting, the temperature of the transfer process can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or 110°C, or any value within the range of 20°C to 110°C.
[0075] Preferably, the transfer pressure is 0-1000 MPa.
[0076] Typically but not limiting, the transfer pressure can be 0 MPa, 100 MPa, 200 MPa, 300 MPa, 400 MPa, 500 MPa, 600 MPa, 700 MPa, 800 MPa, 900 MPa or 1000 MPa, or any value within the range of 0 to 1000 MPa.
[0077] Preferably, the conductive substrate of the semi-finished solar cell sheet comprises ITO glass or FTO glass, preferably ITO glass.
[0078] Solar cells use a conductive substrate because it provides a basis for photoelectric conversion, allowing photogenerated electrons and holes to separate and form current under the action of a built-in electric field. The conductive substrate not only serves as a path for electron transmission, improving cell efficiency, but also serves as an interface for electrode connection, ensuring that photogenerated current can effectively flow from the inside of the cell to the external circuit. In addition, the conductive substrate provides the necessary mechanical support and structural stability for solar cells, protecting the cell from damage from the external environment, and plays a role in cell packaging, enhancing the cell's resistance and life.
[0079] ITO glass, i.e. indium tin oxide coated glass, is made by coating a layer of indium tin oxide film on soda-lime-based or silicon boron-based substrate glass through magnetron sputtering.
[0080] FTO glass, full name Fluorine-doped Tin Oxide glass, is a semiconductor material that achieves conductivity by coating a layer of fluorine-doped Tin Oxide film on the surface of ordinary glass.
[0081] Preferably, the source substrate is made of ITO glass or FTO glass, preferably ITO glass.
[0082] like Figure 1 As shown in the schematic diagram of the passivation process, a side surface with a passivator layer is buckled on the surface of the perovskite layer, and the passivator layer is transferred to the perovskite layer by heating or pressurizing on the source substrate to obtain the passivation layer. Figure 1The left side shows the initial perovskite film. At this time, there are a large number of halogen ion deficiency defects on the surface of the perovskite film. After passivation, these halogen ion deficiency defects are well passivated. At the same time, the long-chain water-transporting end of the passivator faces upward, which can effectively block water and oxygen, thereby improving the stability of the component.
[0083] A second aspect of the present invention provides a process for preparing a perovskite solar cell, comprising the passivation process.
[0084] The preparation process of the perovskite solar cell is to prepare a hole transport layer and a perovskite layer in sequence on a pretreated conductive substrate to obtain a semi-finished solar cell sheet;
[0085] Then, a passivation layer, an electron transport layer, a hole blocking layer and a deposited metal electrode are prepared in sequence on the semi-finished solar cell sheet to obtain the perovskite solar cell.
[0086] The preparation process provided by the present invention, in view of the advantages brought by the above-mentioned passivation process, enables the passivation layer to reduce the recombination phenomenon of electrons on the battery surface, significantly improving the efficiency of solar cells; at the same time, the passivation layer reduces the surface defect density of the battery, reduces the chance of electrons and holes recombination on the surface, thereby improving the performance of the battery. Cooperating with other functional layers, the photoelectric conversion efficiency and battery stability are improved, the production cost is reduced, and the production time is shortened, the production efficiency is improved, and the environmental adaptability and reliability of the battery are enhanced by simplifying and integrating the passivation steps, providing strong support for the large-scale commercial production and technical application of perovskite solar cells.
[0087] Furthermore, the pretreatment process includes P1 scribing, cleaning, drying and activation of the conductive substrate. P1 scribing is a laser scribing process performed on a conductive substrate. The purpose of this step is to form a mutually independent conductive oxide substrate and serve as a positioning point for subsequent P2 and P3 scribing.
[0088] Preferably, the laser frequency of the P1 scribing is 50-500 kHz, and the laser energy is 20-100 μJ.
[0089] Preferably, the width of the P1 scribing line is 80-300 μm, and the speed is 100-300 mm / s.
[0090] Typically but not limiting, the laser frequency of the P1 marking can be 50kHz, 75kHz, 100kHz, 250kHz, 350kHz, 425kHz or 500kHz, or any value in the range of 50kHz to 500kHz; the laser energy can be 20μJ, 30μJ, 40μJ, 60μJ, 80μJ, 90μJ or 100μJ, or any value in the range of 20μJ to 100μJ. In addition, the width of the P1 line can be 80μm, 100μm, 120μm, 160μm, 200μm, 240μm or 300μm, or any value in the range of 80μm to 300μm; the marking rate can be 100mm / s, 150mm / s, 200mm / s, 250mm / s, 275mm / s or 300mm / s, or any value in the range of 100mm / s to 300mm / s.
[0091] Preferably, the cleaning reagents include a cleaning solution specifically for conductive glass, deionized water and an organic solvent used in this order.
[0092] Preferably, the cleaning reagents include a conductive glass cleaning liquid, deionized water and an organic solvent used in sequence to remove impurities and residual organic matter on the conductive substrate. During the cleaning process, the conductive substrate is completely immersed in the liquid and fully in contact with the liquid, thereby achieving a comprehensive cleaning effect.
[0093] Preferably, the organic solvent comprises isopropanol and / or acetone.
[0094] Preferably, the cleaning time of each cleaning reagent is 15 to 25 minutes.
[0095] Typically but not limiting, the cleaning time of each cleaning agent can be 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min or 25 min, or any value within the range of 15 min to 25 min.
[0096] Preferably, the drying method includes drying by oven or air gun to remove the organic solvent remaining on the surface.
[0097] Preferably, the drying temperature is 60-80° C. and the drying time is 18-36 hours.
[0098] Typically but not limitatively, the drying temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, and the time can be 18h, 20h, 24h, 28h, 30h, 32h, 34h or 36h, or any value within the range of 60°C to 80°C and 18h to 36h.
[0099] Preferably, the activation method includes activation by ultraviolet ozone machine or cleaning activation by plasma cleaning machine to improve the wettability of the conductive substrate.
[0100] Preferably, the activation time is 5 to 20 minutes.
[0101] Typically but not limiting, the activation time may be 5 min, 7 min, 10 min, 15 min, 18 min or 20 min, or any value within the range of 5 min to 20 min.
[0102] Furthermore, the preparation method of the hole transport layer is:
[0103] The hole transport layer solution is coated on the pretreated conductive substrate by slit coating, spin coating, magnetron sputtering, scraping, inkjet printing or atomic layer deposition, and then annealed to obtain the hole transport layer.
[0104] During the slit coating process, the hole transport layer is slit coated in an air atmosphere with a relative humidity of 10-50%. The present invention is suitable for industrial production, and all subsequent processes are completed on an automated production line. After the conductive glass substrate is transferred from the assembly line to the slit coating device, it is adsorbed and fixed on the slit coater, and the surface dust is removed by air blowing. 15-30 μL of the configured hole transport layer solution is evenly dripped on one side of the front end, and the distance between the die and the substrate is set to 1.2-1.5 mm, the forward speed of the die is 2-20 mm / s, and the return speed is 5 mm / s. Start the die, and the die moves at a uniform speed in a straight line from one end of the substrate to the other end, coating a uniformly wet film on the substrate.
[0105] Taking magnetron sputtering of nickel oxide as an example, the conductive substrate is transferred to the magnetron sputtering system to deposit the nickel oxide film. A small flow of oxygen can be introduced during the sputtering process to improve the composition of the nickel oxide film. The substrate can be moderately heated during the whole process. The thickness of the nickel oxide is monitored by the crystal oscillator and the film thickness meter. When the thickness meets the requirements, the sputtering is stopped.
[0106] Preferably, the hole transport layer is made of Me-4PACz, PTAA, PETDOS:PSS, CuPc, poly-TPD, 2PACz, MeO-4PADBC or nickel oxide.
[0107] Preferably, the solvent in the hole transport layer solution includes at least one of methanol, chloroform, 2-ME and DMF.
[0108] Preferably, the annealing temperature is 80-120° C. and the annealing time is 8-12 min.
[0109] The annealing process after the hole transport layer is coated is crucial. It not only helps to remove residual solvents, stabilize the crystal structure, and improve electron mobility, but also eliminates impurities and improves crystal quality, thereby improving the photoelectric efficiency of the battery. In addition, annealing further optimizes the photoelectric conversion efficiency and improves the stability and durability of the battery by adjusting the crystallinity and crystal morphology. At the same time, annealing can also improve the surface morphology of the hole transport layer, making it smoother and more uniform, thereby improving contact with the metal electrode, reducing resistance, and facilitating the transmission and collection of electrons. These combined effects significantly improve the performance of perovskite solar cells while ensuring the long-term stability and reliability of the battery.
[0110] Typically but not limiting, the annealing temperature may be 80°C, 90°C, 100°C, 110°C or 120°C, and the annealing time may be 8 min, 9 min, 10 min, 11 min or 12 min, or any value within the range of 80°C to 120°C and 8 min to 12 min.
[0111] Furthermore, the preparation method of the perovskite layer is:
[0112] The perovskite precursor solution is coated on the hole transport layer by slit coating, vacuum evaporation, magnetron sputtering, inkjet printing or doctor blade coating, and then high and low temperature annealing is performed to obtain the perovskite layer.
[0113] The perovskite layer is prepared by the slit coating method. The perovskite layer is slit coated in an air atmosphere with a relative humidity of 10-50%. The conductive glass substrate to be slit coated is placed on a slit coater, and dust on the glass surface is removed by air blowing. It is adsorbed and fixed on the slit coater. 15-30 μL of the configured perovskite precursor solution is evenly dripped on the front end. The distance between the die and the substrate is set to 1.3-1.6 mm, the forward speed of the die is 2-20 mm / s, and the return speed is 15 mm / s. Start the die, and at the same time, turn on the nitrogen air knife to assist in removing the solution. The die moves at a uniform speed from one end of the substrate to the other end, and a uniformly wet film is coated on the substrate. In addition, the deposition method of the perovskite film can also be selected from vacuum evaporation, magnetron sputtering, inkjet printing, scraping and other suitable deposition methods.
[0114] Preferably, the high and low temperature annealing method is to first perform low temperature annealing and then perform high temperature annealing.
[0115] Preferably, the temperature of the low temperature annealing is 60-80°C and the time is 8-12 minutes. The preliminary annealing at a relatively low temperature helps to remove the solvent and avoid too fast a crystallization process. This helps to form a uniform perovskite precursor film, laying the foundation for the next step of high temperature annealing.
[0116] Typically but not limiting, the low temperature annealing temperature can be 60°C, 65°C, 70°C or 80°C, and the time can be 8 min, 9 min, 10 min, 11 min or 12 min, or any value within the range of 60°C to 80°C and 8 to 12 min.
[0117] Preferably, the temperature of the high temperature annealing is 140-160°C and the time is 8-12 minutes. High temperature annealing at a higher temperature helps to promote the crystallization of the perovskite precursor and form uniform and high-quality perovskite crystals. This step is crucial to obtain high-efficiency perovskite solar cells, because uniform perovskite crystals can reduce defects and improve light absorption efficiency, thereby improving the overall performance of the cell.
[0118] Typically but not limiting, the high temperature annealing temperature can be 140°C, 145°C, 150°C, 155°C or 160°C, and the time can be 8 min, 9 min, 10 min, 11 min or 12 min, or any value within the range of 140-160°C and 8-12 min.
[0119] Through this two-step annealing process, the crystallization kinetics of the perovskite layer can be effectively controlled to ensure the uniform growth of the perovskite crystals, which is of great significance for improving the photoelectric conversion efficiency and stability of perovskite solar cells. In addition, this annealing strategy also helps to reduce non-radiative recombination during the battery manufacturing process, improve the open circuit voltage and fill factor of the battery, and further improve the performance of the battery.
[0120] Preferably, the perovskite precursor solution comprises at least one of methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide.
[0121] It should be noted that the present invention does not limit the composition of the perovskite precursor material, and any material that can form a perovskite layer can be used. The selected perovskite component can be at least one of methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide, or it can be replaced or added with other suitable materials such as methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide, and their various permutations and combinations of different materials, and the molar ratio of various components can be appropriately adjusted. The solvent of the selected perovskite precursor solution can also replace or add other suitable reagents such as 2-Me, DMSO, DMPU and their permutations and combinations, and the volume ratio of various reagents can be adjusted to obtain a perovskite light absorption layer with different band gaps and different performances.
[0122] Preferably, the solvent in the perovskite precursor solution includes at least one of DMF, NMP, DMSO and DMPU.
[0123] It should be noted that if the vacuum flash evaporation method is used, only one-step annealing, that is, high-temperature annealing, is required to obtain a uniformly crystalline perovskite layer.
[0124] Furthermore, the preparation method of the electron transport layer is:
[0125] The electron transport layer material is deposited on the passivation layer by vacuum evaporation, magnetron sputtering or atomic layer deposition to obtain the electron transport layer.
[0126] Preferably, the thickness of the electron transport layer is 20-60 nm. The deposition rate of the electron transport layer can be controlled between 0.005-0.02 nm / s, and the deposition thickness can be selected to be a suitable thickness between 20-60 nm.
[0127] Typically but not limiting, the thickness of the electron transport layer may be 20 nm, 30 nm, 40 nm, 50 nm or 60 nm, or any value within the range of 20 nm to 60 nm.
[0128] Preferably, the electron transport layer material comprises C60, PCBM, titanium dioxide, zinc oxide or tin dioxide. PCBM is [6.6]-phenyl-C 61 -Methyl butyrate.
[0129] Among the above-mentioned electron transport layer materials, C60 and PCBM can be prepared by vacuum thermal evaporation, spin coating or slit coating. In vacuum thermal evaporation, the vacuum degree of the equipment is 10 -4 ~10 -5 Pa. Titanium dioxide and zinc oxide can be deposited by magnetron sputtering. The vacuum degree of magnetron sputtering equipment is 10 -4 ~10 -5 Pa. Tin dioxide can be deposited by atomic layer deposition (ALD) and the deposition rate can be controlled between 0.005-0.02 nm / s.
[0130] Furthermore, the preparation method of the hole blocking layer is:
[0131] The hole blocking layer material is deposited on the electron transport layer by vacuum evaporation or atomic layer deposition to obtain the hole blocking layer.
[0132] Preferably, the thickness of the hole blocking layer is 6-7 nm. The hole blocking layer deposition rate can be selected from a range of 0.001-0.003 nm / s, and the deposition thickness can be selected from a range of 6-7 nm.
[0133] In some embodiments of the present invention, a layer of LiF or other suitable materials may be deposited on the hole blocking layer by a suitable method as a buffer layer, mainly to improve the electron transmission performance, reduce interface recombination, improve battery stability, effectively block ion migration, protect the light absorption layer from oxidative decomposition of water molecules and oxygen, reduce leakage current, and improve battery hysteresis. The introduction of such a buffer layer helps to optimize the transmission of electrons and holes, reduce non-radiative recombination at the interface, and protect the battery from environmental factors, thereby improving the efficiency and stability of the solar cell.
[0134] Preferably, the hole blocking layer material includes BCP or tin dioxide.
[0135] BCP can be vacuum-evaporated (the vacuum degree of the equipment is 10 -4 to 10 -5 Tin dioxide can be deposited by atomic layer deposition (ALD).
[0136] Furthermore, the preparation process of the perovskite solar cell also includes P2 scribing after the hole blocking layer is prepared and before the metal electrode is deposited. The purpose of P2 scribing is to etch the hole transport layer, the perovskite layer, the passivation layer, the electron transport layer, and the hole blocking layer, exposing the conductive layer on the conductive substrate so that the metal electrode deposited in the next step is in direct contact with the conductive layer to achieve positive and negative connection between the sub-cells. Provide a transmission channel for the positive and negative electrodes of two adjacent sub-cells.
[0137] Preferably, the laser frequency of the P2 scribing is 50-500 kHz, and the laser energy is 20-100 μJ.
[0138] Preferably, the width of the P2 scribing line is 40-300 μm, and the speed is 50-500 mm / s.
[0139] Typically but not limiting, the laser frequency of the P2 scribing line can be 50kHz, 100kHz, 200kHz, 300kHz, 400kHz or 500kHz, and the laser energy can be 20μJ, 40μJ, 60μJ, 80μJ or 100μJ, or any value within the range of 50kHz to 500kHz and 20μJ to 100μJ. The width of the P2 scribing line can be 40μm, 100μm, 160μm, 220μm or 300μm, and the speed can be 50mm / s, 100mm / s, 200mm / s, 300mm / s, 400mm / s or 500mm / s.
[0140] Preferably, the electrode material is deposited by vacuum evaporation to obtain the metal electrode. The metal electrode is deposited by vacuum thermal evaporation. The electrode material to be deposited can be a suitable conductive material such as copper, silver and gold. The vacuum degree of the equipment can be 10 -4 Pa to 5×10 -4 Within the Pa range, the deposition rate can be selected from 0.02-0.1 nm / s, and the deposition thickness can be selected from 50-200 nm. The deposition technology can also be selected from other suitable methods such as printing.
[0141] Preferably, the thickness of the metal electrode is 50-200 nm. Typically but not limiting, the thickness of the metal electrode may be 50 nm, 75 nm, 100 nm, 125 nm, 150 nm, 175 nm or 200 nm, or any value within the range of 50 nm to 200 nm.
[0142] Preferably, the electrode material includes copper, silver or gold.
[0143] Picosecond laser is used to perform P3 scribing to separate the sub-cells. The frequency of laser scribing can be selected in the range of 50-500kHz, the energy can be selected in the range of 20-100μJ, the width can be selected in the range of 40-300μm, and the speed can be selected in the range of 50-500mm / s.
[0144] P3 scribing is performed after the metal electrode layer is prepared. Its purpose is to separate the sub-batteries to form separate modules that block current conduction, so as to achieve the effect of increasing voltage and connecting batteries in series.
[0145] P4 scribing, also known as laser edge cleaning, is a process for cleaning the edge of the cell. The purpose is to remove the film layer of about 10mm width near the edge of the glass to form an insulating area as the back-end packaging area. This step helps to ensure the insulation of the edge of the cell, prevent short circuits and leakage, and also helps to improve the overall packaging quality of the cell.
[0146] The P4 scribing frequency can be appropriately selected within the range of 10 to 100 kHz, the energy can be appropriately selected within the range of 10 to 50 μJ, and the speed can be appropriately selected within the range of 100 to 1000 mm / s.
[0147] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0148] Example 1
[0149] This embodiment provides a perovskite solar cell, comprising the following steps:
[0150] 1. The transparent conductive glass adopts ITO substrate, and the selected 2 , the frequency of P1 laser scribing is 200kHz, the energy is 50μJ, and the width is 100μm.
[0151] 2. Ultrasonic cleaning of ITO substrate, the cleaning agents are conductive glass cleaning liquid, deionized water, isopropyl alcohol. The conductive glass substrate should be completely immersed in the liquid, and each cleaning agent should be cleaned for 20 minutes. Take out the cleaned conductive glass substrate and dry it in a drying oven. The drying temperature is set to 70℃ and the time is 24 hours.
[0152] 3. Take out the dried ITO substrate and transfer it to the UVO ozone analyzer to clean and activate the glass surface for 15 minutes.
[0153] 4. Prepare the hole transport layer solution, dissolve 1 mg of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (i.e. Me-4PACz) in 1 mL of methanol:chloroform solvent (volume ratio of 1:1), shake thoroughly for 10 hours and filter. Prepare the hole transport layer by slit coating, and coat the hole transport layer in an air atmosphere with a relative humidity of 25%. First, clean the liquid inlet pipe of the slit coater with a blank solvent, and then apply 20 mL of the prepared hole transport layer solution. Place the ITO substrate to be coated in the slit coater, adsorb and fix it on the base, remove the dust on the surface with air blowing, set the length, width and thickness of the substrate, use 20 μL of hole transport layer solution per piece, the distance between the die and the substrate is 1.35 mm, the forward speed of the die is 10 mm / s, start coating, and the die moves relatively from one end of the substrate to the other end at a uniform linear speed, coating a uniformly wet film on the substrate. The substrate coated with the hole transport layer was transferred to a hot stage and annealed at 100 °C for 10 min.
[0154] 5. Configure Rb 0.05 Cs 0.05 MA 0.1 FA 0.8PbI3 perovskite precursor solution, 0.5071g of lead iodide, 0.09g of methylamine hydroiodide, 0.09g of formamidine hydroiodide, 0.0143g of cesium iodide and 0.0143g of rubidium iodide are mixed and dissolved in 1mL2-ME and DMSO mixed solvent to prepare a perovskite precursor solution, which is fully shaken for 10 hours and then filtered. The perovskite layer is prepared by the slit coating method. The perovskite layer is coated in an air atmosphere with a relative humidity of 25%. The plunger pump, die head and liquid inlet pipeline are first cleaned with DMF solvent, and then the conductive glass substrate to be coated is placed on the slit coater, and the dust on the glass surface is removed by air blowing. It is adsorbed and fixed on the coating base, and the length, width and thickness of the substrate are set. The amount of perovskite precursor solution per piece can be 20μL, the distance between the die head and the substrate is 1.35mm, and the die head advances at a speed of 10mm / s. Start coating, the die head moves relatively from one end of the substrate to the other end at a constant speed, and a uniform wet film is coated on the substrate. Instead of using a nitrogen air knife to assist, the solution can be removed by vacuum flash evaporation, and the vacuum degree can be drawn to less than 1Pa.
[0155] The substrate coated with the perovskite precursor solution was transferred to a hot stage, first annealed on a 70°C hot stage for 10 min, and then quickly transferred to a 150°C hot stage for annealing for 10 min to obtain a uniformly crystalline perovskite layer.
[0156] 6. A layer of PEAI passivation molecules is slit coated on a clean FTO substrate, and then the front side of the substrate is buckled onto the upper surface of the perovskite film by an automated device. The transfer of the passivation agent molecules from the blank substrate to the surface of the perovskite film is promoted at 60°C and 20MPa for 10 minutes, thereby passivating the surface and interface defects of the large-area perovskite film to obtain a passivation layer.
[0157] 7. The electron transport layer material is C 60 , using vacuum thermal evaporation method, the vacuum degree of the equipment is 2×10 -4 Pa, the evaporation current is 40A, the deposition rate is 0.01nm / s, and the deposition thickness is 30nm.
[0158] 8. The hole blocking layer material is BCP, and the vacuum thermal evaporation method is adopted. The vacuum degree of the equipment is 2×10 -4 Pa, the evaporation temperature is 230℃, the evaporation voltage is 2.9V, the deposition rate is 0.002nm / s, and the deposition thickness is 6.5nm.
[0159] 9. Picosecond laser is used for P2 scribing. The frequency of laser scribing is 200kHz, the energy is 48.5μJ, the width is 50μm, and the speed is 200mm / s.
[0160] 10. Copper is deposited by vacuum thermal evaporation method, and the vacuum degree of electrode equipment is 2×10 -4Pa. The deposition rate was 0.05 nm / s, the deposition thickness was 100 nm, and a copper electrode was obtained.
[0161] 11. Picosecond laser is used for P3 scribing. The frequency of laser scribing is 200kHz, the energy is 48.5μJ, the width is 50μm, and the speed is 200mm / s.
[0162] 12. Use P4 scribing to clean the edges and remove the residual impurities of P2 and P3 scribing to avoid short circuits. The frequency of laser scribing is 100kHz, the energy is 20μJ, the width is 100μm, and the speed is 500mm / s.
[0163] 13. Use encapsulation glue to encapsulate the components. On the bottom side, use UV resin to encapsulate the perovskite component through a 1mm thick glass substrate and anneal at 80℃ for 30s. Then use hot press bonding resin to encapsulate through a 1mm thick glass substrate on the top side and then anneal at 80℃ for 30s. Coat the edge of the module with UV resin encapsulation and irradiate with a 4W UV lamp for 30s to obtain a perovskite solar cell.
[0164] Example 2
[0165] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0166] 4. Transfer the ITO substrate to the magnetron sputtering system to deposit the nickel oxide film. The pressure of the system is 5×10 -4 Pa. A small flow of oxygen was introduced during the sputtering process to improve the composition of the nickel oxide film. The substrate was heated moderately during the whole process. The thickness of the nickel oxide was monitored by a crystal oscillator and a film thickness meter. The deposition thickness was about 40nm. The substrate coated with the hole transport layer was transferred to a hot stage and annealed at 100℃ for 10min.
[0167] The remaining steps are the same as those in Example 1 and will not be described again.
[0168] Example 3
[0169] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0170] 6. A layer of 4-trifluoromethylphenylethylamine iodine molecules is slit coated on a clean FTO substrate, and then the front side of the substrate is buckled on the upper surface of the perovskite film by an automated device. The passivator molecules are transferred from the blank substrate to the surface of the perovskite film at 60°C and 20MPa for 10 minutes, thereby passivating the surface and interface defects of the large-area perovskite film to obtain a passivation layer.
[0171] The remaining steps are the same as those in Example 1 and will not be described again.
[0172] Example 4
[0173] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0174] 6. A layer of cycloheximide-N-nitrobenzoate molecules is slit coated on a clean FTO substrate, and then the front side of the substrate is buckled on the upper surface of the perovskite film through an automated device. The passivator molecules are transferred from the blank substrate to the surface of the perovskite film at 60°C and 20MPa for 10 minutes, thereby passivating the surface and interface defects of the large-area perovskite film to obtain a passivation layer.
[0175] The remaining steps are the same as those in Example 1 and will not be described again.
[0176] Example 5
[0177] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0178] 6. A layer of ethylenediamine iodine molecules is slit coated on a clean FTO substrate, and then the front side of the substrate is buckled onto the upper surface of the perovskite film by an automated device. The transfer of the passivator molecules from the blank substrate to the surface of the perovskite film is promoted at 60°C and 20MPa for 10 minutes, thereby passivating the surface and interface defects of the large-area perovskite film to obtain a passivation layer.
[0179] The remaining steps are the same as those in Example 1 and will not be described again.
[0180] Example 6
[0181] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0182] 6. A layer of diaminobutane molecules is slit coated on a clean FTO substrate, and then the front side of the substrate is buckled on the upper surface of the perovskite film by an automated device. The transfer of the passivator molecules from the blank substrate to the surface of the perovskite film is promoted at 60°C and 20MPa for 10 minutes, thereby passivating the surface and interface defects of the large-area perovskite film to obtain a passivation layer.
[0183] The remaining steps are the same as those in Example 1 and will not be described again.
[0184] Example 7
[0185] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0186] 6. A layer of PEAI passivation molecules is slit coated on a clean FTO substrate, and then the front side of the substrate is buckled onto the upper surface of the perovskite film by an automated device. The transfer of the passivation agent molecules from the blank substrate to the surface of the perovskite film is promoted at 20°C and 20 MPa for 10 minutes, thereby passivating the surface and interface defects of the large-area perovskite film to obtain a passivation layer.
[0187] The remaining steps are the same as those in Example 1 and will not be described again.
[0188] Example 8
[0189] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0190] 6. A layer of PEAI passivation molecules is slit coated on a clean FTO substrate, and then the front side of the substrate is buckled onto the upper surface of the perovskite film through an automated device. The transfer of the passivation agent molecules from the blank substrate to the surface of the perovskite film is promoted at 110°C and 20MPa for 10 minutes, thereby passivating the surface and interface defects of the large-area perovskite film to obtain a passivation layer.
[0191] The remaining steps are the same as those in Example 1 and will not be described again.
[0192] Example 9
[0193] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0194] 6. A layer of PEAI passivation molecules is slit coated on a clean FTO substrate, and then the front side of the substrate is buckled onto the upper surface of the perovskite film through an automated device. The transfer of the passivation agent molecules from the blank substrate to the surface of the perovskite film is promoted at 60°C and 100 MPa for 10 minutes, thereby passivating the surface and interface defects of the large-area perovskite film to obtain a passivation layer.
[0195] The remaining steps are the same as those in Example 1 and will not be described again.
[0196] Example 10
[0197] This embodiment provides a perovskite solar cell, which is different from Embodiment 1 in that:
[0198] 6. A layer of PEAI passivation molecules is slit coated on a clean FTO substrate, and then the front side of the substrate is buckled onto the upper surface of the perovskite film by an automated device. The transfer of the passivation agent molecules from the blank substrate to the surface of the perovskite film is promoted at 60°C and 20MPa for 5 minutes, thereby passivating the surface and interface defects of the large-area perovskite film to obtain a passivation layer.
[0199] The remaining steps are the same as those in Example 1 and will not be described again.
[0200] Comparative Example 1
[0201] This comparative example provides a perovskite solar cell, which is different from Example 1 in that:
[0202] 6. The passivation agent PEAI (phenylethylamine iodide) was directly coated on the perovskite layer by a slit coating method. The solution concentration was 1 mg / mL, the solvent was isopropanol, the coating forward speed was 10 mm / s, and the annealing parameters were 80° C. for 5 min to obtain a passivation layer.
[0203] The remaining steps are the same as those in Example 1 and will not be described again.
[0204] Comparative Example 2
[0205] This comparative example provides a perovskite solar cell, which is different from Example 1 in that:
[0206] 6. The interface of the perovskite layer is modified by the vapor phase passivation method. In a sealed container, the conductive substrate containing the perovskite layer is first suspended upside down, and an isopropanol solution of 4-trifluoromethylphenylethylamine iodine (4-CF3-PEAI) is placed underneath as a passivating agent. It is heated at 80°C to volatilize it and fully passivate the surface and interface defects of the perovskite for 10 minutes.
[0207] The remaining steps are the same as those in Example 1 and will not be described again.
[0208] Test Example 1
[0209] The semi-finished solar cells of Example 1 and Comparative Example 1 after step 6 were subjected to fluorescence spectroscopy. The obtained spectral graphs are as follows: Figure 2 shown.
[0210] Figure 2 As shown in the fluorescence spectrum, when the physical and chemical properties of the film are similar, the higher the fluorescence intensity, the lower the defect state density. Reducing the surface defect state density helps to suppress the non-radiative recombination of the surface interface, thereby improving the efficiency of large-area components. Figure 2 It can be found that the defect state density of Example 1 is significantly lower than that of Comparative Example 1. The passivation method of Example 1 can improve the efficiency of large-area perovskite components.
[0211] Test Example 2
[0212] The solar cells obtained in Example 1 and Comparative Example 1 were subjected to IV curves. Figure 3 shown.
[0213] from Figure 3It can be seen that Example 1 has a higher open circuit voltage (VOC) and fill factor (FF), which further indicates that the passivation method of Example 1 can significantly reduce the surface and interface defects of large-area perovskite films, which is consistent with the fluorescence spectroscopy characterization results.
[0214] Test Example 3
[0215] The perovskite solar cells provided in the embodiments and comparative examples are subjected to performance tests to obtain the open circuit voltage V of the corresponding solar cells. oc , short circuit current density J sc , fill factor FF, photoelectric conversion efficiency PCE, the test results are shown in Table 1.
[0216] Table 1
[0217]
[0218]
[0219] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A passivation process for a perovskite layer, characterized in that: Laminating a source substrate with a passivation layer to a semi-finished solar cell, and transferring the passivation layer to a surface of the semi-finished solar cell to obtain a passivation layer; The surface layer of the semi-finished solar cell sheet is a perovskite layer.
2. The passivation process according to claim 1, characterized in that: The transfer temperature is 20 to 110° C. Preferably, the transfer pressure is 0-1000Mpa; Preferably, the conductive substrate of the semi-finished solar cell sheet comprises ITO glass or FTO glass, preferably ITO glass; Preferably, the source substrate is made of ITO glass or FTO glass, preferably ITO glass; Preferably, the surface of one side with the passivator layer is placed on the surface of the perovskite layer, and the passivator layer is transferred to the perovskite layer by heating or pressurizing on the source substrate to obtain the passivation layer.
3. A process for preparing a perovskite solar cell, characterized in that: The invention comprises the passivation process as claimed in claim 1 or 2.
4. The preparation process according to claim 3, characterized in that: A hole transport layer and a perovskite layer are prepared in sequence on the pretreated conductive substrate to obtain a semi-finished solar cell; Then, a passivation layer, an electron transport layer, a hole blocking layer and a deposited metal electrode are prepared in sequence on the semi-finished solar cell sheet to obtain the perovskite solar cell.
5. The preparation process according to claim 4, characterized in that: The pretreatment process includes P1 scribing, cleaning, drying and activation of the conductive substrate; Preferably, the laser frequency of the P1 scribing is 50-500kHz, and the laser energy is 20-100μJ; Preferably, the width of the P1 scribing line is 80-300 μm, and the speed is 100-300 mm / s; Preferably, the cleaning reagents include a cleaning solution for conductive glass, deionized water and an organic solvent used in this order; Preferably, the organic solvent comprises isopropanol and / or acetone; Preferably, the cleaning time of each cleaning reagent is 15 to 25 minutes; Preferably, the drying method includes drying by oven drying or air gun drying; Preferably, the drying temperature is 60-80°C and the drying time is 18-36h; Preferably, the activation method includes ultraviolet ozone machine activation or plasma cleaning machine cleaning activation; Preferably, the activation time is 5 to 20 minutes.
6. The preparation process according to claim 4, characterized in that: The preparation method of the hole transport layer is as follows: The hole transport layer solution is coated on the pretreated conductive substrate by slit coating, spin coating, magnetron sputtering, doctor blading, inkjet printing or atomic layer deposition, and then annealed to obtain the hole transport layer; Preferably, the hole transport layer is made of Me-4PACz, PTAA, PETDOS:PSS, CuPc, poly-TPD, 2PACz, MeO-4PADBC or nickel oxide; Preferably, the solvent in the hole transport layer solution includes at least one of methanol, chloroform, 2-ME and DMF; Preferably, the annealing temperature is 80-120° C. and the annealing time is 8-12 min.
7. The preparation process according to claim 4, characterized in that: The preparation method of the perovskite layer is: The perovskite precursor solution is coated on the hole transport layer by slit coating, vacuum evaporation, magnetron sputtering, inkjet printing or doctor blade coating, and then high and low temperature annealing is performed to obtain a perovskite layer; Preferably, the high and low temperature annealing method is to first perform low temperature annealing and then perform high temperature annealing; Preferably, the low temperature annealing temperature is 60-80°C and the time is 8-12 minutes; Preferably, the high temperature annealing temperature is 140-160°C and the time is 8-12 minutes; Preferably, the perovskite precursor solution includes at least one of methylamine hydroiodide, formamidine hydroiodide, rubidium iodide, lead iodide and lead bromide; Preferably, the solvent in the perovskite precursor solution includes at least one of DMF, NMP, DMSO and DMPU.
8. The preparation process according to claim 4, characterized in that: The preparation method of the electron transport layer is as follows: Depositing the electron transport layer material on the passivation layer by vacuum evaporation, magnetron sputtering or atomic layer deposition to obtain the electron transport layer; Preferably, the thickness of the electron transport layer is 20 to 60 nm; Preferably, the electron transport layer material includes C60, PCBM, titanium dioxide, zinc oxide or tin dioxide.
9. The preparation process according to claim 4, characterized in that: The preparation method of the hole blocking layer is as follows: Depositing the hole blocking layer material on the electron transport layer by vacuum evaporation or atomic layer deposition to obtain the hole blocking layer; Preferably, the thickness of the hole blocking layer is 6 to 7 nm; Preferably, the hole blocking layer material includes BCP or tin dioxide.
10. The preparation process according to claim 4, characterized in that: Also included is P2 scribing after preparing the hole blocking layer and before depositing the metal electrode; Preferably, the laser frequency of the P2 scribing is 50-500kHz, and the laser energy is 20-100μJ; Preferably, the width of the P2 scribing line is 40-300 μm, and the speed is 50-500 mm / s; Preferably, the electrode material is deposited by vacuum evaporation to obtain a metal electrode; Preferably, the thickness of the metal electrode is 50 to 200 nm; Preferably, the electrode material includes copper, silver or gold.
Citation Information
Cited By
In-situ bulk phase passivation method and system of perovskite thin film and perovskite photoelectric device
CN121442938A